Way Forward in Process Safety Management (PSM) for Effective Implementation in Process Industries - Azmi, Mohd Shariff; Hanida, Abdul Aziz; Noor Diana, Abdul Majid (Elsevier Ltd, 2016)
This paper addressed the issues in implementing Process Safety Management (PSM) as stipulated by OSHA regulations in 1992 in process industries. The purpose of PSM implementation is to prevent major accidents such as fire,explosion and toxic release. Unfortunately, after more than 20 years of implementation, major accidents are still occurring in process plant that is covered under the PSM standard. The issues faced by industries to implement the PSM program effectively are thoroughly discussed. Recommendations to improve the PSM program are provided as an opportunity for researchers and practitioners to further develop the PSM system for effective implementation in process industries.